PERTUMBUHAN BIBIT KELAPA SAWIT (ELAEISGUINENSISJACQ.) MAIN NUSERYPADA MEDIA GAMBUT YANG DI APLIKASI KOMBINASI DOLOMIT DAN PUPUK ZINKCUP MELALUI DAUN - Rizal Joko Joko Purnomo; Wawan Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
1.2. Oil palm is a crop that has high economic value and is suitable for cultivation in tropical climates such as Indonesia. The development of oil palm plantations continues to be carried out because it is an oil-producing commodity consisting of crude CPO and kernel. Riau province has a very large area of peat land.Peat land has great potential for agricultural cultivation. Availability of macro and micro nutrients in peat soil has a low content. The main keys to the success of crop cultivation on peatlands are increasing soil pH, availability of nutrients for plants and reducing the activity of toxic organic monomeric acids. The method commonly used to improve problematic land includes liming. One type of fertilization that is carried out is fertilization through leaves. This study aims to determine the growth of oil palm seedlings on peat soil by applying dolomite and micro fertilizers through the leaves, knowing the best dosage for oil palm seedling growth and knowing the interaction of dolomite fertilizer with micro fertilizers. This research was conducted in the experimental garden of the Faculty of Agriculture, University of Riau. This research has been conducted for three months from October to December 2019. Based on the results of the research that has been carried out, it can be concluded that Zinkcup fertilizer given to plants can increase the growth of oil palm seedlings in peat media, application of 3 g micro fertilizer doses through leaves and 12.5 g dolomite fertilizer was able to increase the growth of oil palm seedlings in peat media and the interaction between the application of 3 g micro fertilizer through leaves and 12.5 g dolomite fertilizer resulted in good growth of oil palm seedlings in the media peat. Key words: oil palm, dolomite, zinccup, peat